The Effect of Digital Banking, Digital Financial Literacy, and Service Innovation on Customer Loyalty Through Digital Banking Application User Satisfaction - Pratiwi, Suci Kurnia (Journal Research of Social Science, Economics, and Management, 2026)
The development of digital technology encourages banks to improve the quality of services through digital banking to maintain customer loyalty. This study aims to analyze the influence of digital banking, financial literacy, and service innovation on customer loyalty through the satisfaction of digital banking application users at Bank BJB Cilegon Branch. This study used a quantitative approach with a survey method through the distribution of questionnaires to users of the digital banking application of Bank BJB Cilegon Branch. The data obtained was analyzed using statistical analysis to test the influence of variables partially or simultaneously, as well as test the role of user satisfaction as a mediating variable. The results of the study show that digital banking has a positive and significant effect on the loyalty of digital banking application users. Digital financial literacy has also been proven to have a positive and significant effect on user loyalty, which shows that customer understanding and ability to manage digital financial services encourages increased loyalty. In addition, service innovation has a positive and significant effect on the loyalty of digital banking application users. User satisfaction has a strong influence on user loyalty, where a high level of satisfaction will increase customer loyalty in using digital banking applications. Simultaneously, digital banking, financial literacy, and service innovation have a positive and significant effect on customer loyalty through user satisfaction of digital banking applications.